(untitled) (Journal of Gender and Social Issues, 2017)
The objectives of this study were to explore the socio-economic conditions of women workers and their experiences. The paper begins with a brief overview of policies of economic restructuring namely trade liberalization, privatization and fiscal austerity which have drawn map for changes in the economy and through the establishment of export-oriented industries. Qualitative and quantitative methods were used to collect primary data by implementing questionnaires and by listening to women workers? narratives. Results show that formal jobs for women were already low, while informal and contract based jobs is increasing. Along with that, in some sectors, more women are hired because of their perceived docile, tolerant behaviour and their satisfaction with substandard wages. Majority of women hired in textile and garments are on assembly line jobs. High inflation, no job security and absence of unions in EPZ makes it difficult for women to get decent work opportunities.